Litterfall Production and Decomposition in Three Types of Land Use in Bengkulu Protection Forest - Enggar Apriyanto; Fajrin Hidayat; Putranto BA Nugroho; Imanta Tarigan (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
Most of the social forestry program plantations in Bengkulu are in the form of mixed planting of coffee or rubber trees. The type of land use affects the production and decomposition of litterfall, which play an important role in nutrient cycle. The aim of the research was to determine the production and decomposition rate of litterfall in coffee (Coffee robusta) monoculture, coffee and Gliricidia sepium (gliricidia) agroforestry, and rubber (Hevea brasiliensis) monoculture. The research was arranged in a systematic design with three treatments and fifteen replications. The variables measured included production, composition, and decomposition rate of litterfall. The collected data were analyzed using T-test. According to the results, the litter production in coffee monoculture, agroforestry of coffee and gliricidia, and rubber monoculture was 1051.5, 1001.5, and 662.5 Kg ha-1 4 months-1 with the decomposition rate about 5.13, 4.25, and 5.28 gr m-2 4 months-1, consecutively.  The litterfall composition in the three types of land use consisted of leaf, twig, fruit, and flower. Leaf was the highest component of litterfall in coffee monoculture, agroforestry of coffee and gliricidia, and rubber monoculture, reaching 830.2 (78.99%), 646.7 (64.73%), and 391.0 (59.01%) kg ha-1, respectively. Nutrition analysis of leaf litterfall indicated that the highest content of C, N, P, and K was observed in agroforestry of coffee and gliricidia compared to other plantation types.